SILARIANG DALAM PERSPEKTIF HUKUM ISLAM (Studi Kasus di Kabupaten Sidrap) - Wirani Aisiyah Anwar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
Silariang is talking about marriage commit in situation that man and woman sneak of and like each other and do marriage process by no buginese elaborate ceremonies and agreement from both of family or representative from bride side by particular reason in sidrap regency. This research purposes to understand about silariang marriage in sidrap regency. The impact and legal review about silariang marriage by using qualitative describtive method and effort to know and understand the phenomena. Data acquired by interview and documentation study. The research show that the process of silariang marriage (Illegal marriage) in sidrap regency because some factor that is: love feeling didn’t get be controlled between couple has not make marriage relationship, uang panai is too high. Woman/ man family didn’t agree to their child choice because they are not of the same level. Man/ woman introduced to family has bad behavior and not at the same religion. Silariang gives bad impact to person and their family because silariang is rated as scandal but as times go on, the hard cultural punishment is eroding. Showed by overcome the silariang person, when they come back to their hometown, most of them just be re-marriage by tradition and forget the case happened